Radiographic Assessment of Alveolar Bone Crest Levels in 9-12 Year Old Children in Davangere, India - KL, Vandana; Ghosh, Saubhik (International Journal of Medical and Health Sciences Research, 2014)
Background: Recent studies have indicated that aggressive periodontitis in the permanent dentition of adolescents often is preceded by bone loss in the primary and mixed dentition. Hence it is necessary to detect and treat these patients for preventing the transition of the disease from primary to permanent dentition. Aims and Objectives: The aim of this study was to radiographically determine the cemento-enamel junction (CEJ) to alveolar bone crest (ABC) distance in the interproximal areas of permanent molars and central incisors during the mixed dentition period. Materials and Methods: The study was a cross sectional study spanned over a period of one year. Panoramic radiographs were taken for 410 children residing in Davangere, Karnataka aged between 9-12 years. CEJ-ABC distance was measured at the mesial and distal surfaces of permanent first molars and permanent central incisors. Statistical analysis: Independent t-test was applied to compare CEJ–ABC distances measured in males and females, in the two age groups, the maxillary permanent central incisors and maxillary permanent first molars, the maxillary permanent first molars and mandibular permanent first molars. Results: The CEJ-ABC distance was less than 2mm in more than 95% of the sites. In some of the sites the distance when it was more than 2mm could be suggestive of normal physiology during mixed dentition period. Conclusion: The radiographic distance between CEJ-ABC if more than 2mm could be physiologic and hence requires to be deciphered by clinical evaluation.